Signatures of reionization feedback in the near-infrared background. Issue 3 (8th September 2022) - Mirocha, Jordan; Liu, Adrian; La Plante, Paul
ABSTRACT: The reionization of the intergalactic medium at redshifts z ≳ 6 is expected to have a lasting impact on galaxies residing in low-mass dark matter haloes. Unable to accrete or retain gas photoheated to temperatures T ≳ 10 4 K, the star formation histories of faint galaxies in the early Universe are expected to decline as they exhaust their gas supply, and so give rise to a 'turnover' at the faint-end of the galaxy luminosity function. In this work, we explore the possibility of constraining this reionization feedback with measurements of the cosmic near-infrared background (NIRB), which traces the rest-optical and ultraviolet emission of high-redshift galaxies. We find that the contrast between passively-ageing low-mass galaxies quenched by reionization and bluer actively star-forming galaxies unaffected by reionization, manifests as a scale- and colour-dependent signature in the NIRB at a level comparable to the sensitivity of NASA's upcoming SPHEREx mission. Whereas models with pure mass suppression largely affect the signal at wavelengths ≲2 μm, ∼5 per cent-level differences in the background persist out to ≃5 μm for reionization feedback models on ≃20 arcmin scales. Finally, the power spectra of intensity ratio maps exhibit larger ∼ tens of per cent variations, and may thus be a promising target for future analyses.